2021
DOI: 10.37349/emed.2021.00037
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic manifestations of drug reaction with eosinophilia and systemic symptoms syndrome

Abstract: Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a potentially life-threatening drug reaction, which can affect multiple organs. Patients with DRESS syndrome and hepatic manifestations may present alterations ranging from mild hepatitis to acute liver failure. The diagnosis might be difficult, and the management of these patients is challenging. This report analyzes a series of five cases reporting the clinical presentation, which ranged from acute hepatitis to liver failure, and discu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…This review identified antibiotics as the drug class most frequently causing DS, with vancomycin being the most common. Similar findings of antibiotics as the most common class of medication associated with DS were observed in other retrospective studies [98,100], a case series [101], and in recent literature reviews [8,99]. Allopurinol, which was associated with a higher risk of renal involvement in some studies [85,90], is the second most common causative agent of DS in this review.…”
Section: Causative Drugs and Latencysupporting
confidence: 89%
See 1 more Smart Citation
“…This review identified antibiotics as the drug class most frequently causing DS, with vancomycin being the most common. Similar findings of antibiotics as the most common class of medication associated with DS were observed in other retrospective studies [98,100], a case series [101], and in recent literature reviews [8,99]. Allopurinol, which was associated with a higher risk of renal involvement in some studies [85,90], is the second most common causative agent of DS in this review.…”
Section: Causative Drugs and Latencysupporting
confidence: 89%
“…Allopurinol, which was associated with a higher risk of renal involvement in some studies [85,90], is the second most common causative agent of DS in this review. Interestingly, anticonvulsants appeared as the third most common in our review, and in many previous studies, it was identified as the main causative class [89,95,96,[101][102][103]. It remains to be answered in future studies if certain medication classes have the predisposition to cause particular visceral manifestations of DS.…”
Section: Causative Drugs and Latencymentioning
confidence: 66%
“…It is described that patients with severe acute liver damage may shows an overall survival of 75%, with hepatic encephalopathy, factor V level, prothrombin time were predictors of poor prognosis. 9 Lung involvement from DRESS may decrease lung capacity as this condition may take form as acute interstitial pneumonitis, lymphocytic interstitial pneumonia, pleuritis, and acute respiratory distress syndrome (ARDS). Lung involvement may also be described by signs such as cough, dyspnea, pleuritic pain and/or radiological findings such as unilateral or bilateral pulmonary infiltrates, lobar infiltrates, and pulmonary nodules.…”
Section: Discussionmentioning
confidence: 99%